Managing marine fishery in Kerala through simulation using surplus production model, genetic algorithm and spectral methods - Sathianandan, T V; Jayasnakar, J (Indian Journal of Fisheries, 2016)
Outboard ring seines and mechanized trawl nets form the two major fisheries in Kerala accounting for about 72% of the total catch in the state. A genetic algorithm was developed for simulation of trawl net and ring seine fishery using surplus production model and spectral methods. Simulations were carried out for six different levels of exploitations and the average biomass and average yield were calculated and compared with the maximum sustainable yield (MSY). The simulation results based on ring seine fishery revealed that the optimum level of exploitation is at 86.3% of the current level of exploitation to keep the annual average yields during 2005-2014 just below MSY, for both oil sardine and mackerel. Simulations based on trawl net fishery suggested maintaining the exploitation level at 87.9% of the current level to retain the average annual yields of penaeid prawns, cephalopods and threadfin breams below the MSY level during 2005-2013.